IDENTIFIKASI KESULITAN BELAJAR MATEMATIKA SISWA KELAS IV PADA MATERI KPK DAN FPB DI SDN 03 SUKA MAKMUR KECAMATAN GERUNG - Asmawati, Lia; Husniati, Husniati; Niswatul Khair, Baiq (Jurusan Ilmu Pendidikan FKIP Universitas Mataram, 2023)
Descriptive qualitative research is a study to identify difficulties in learning mathematics students on the material of KPK and FPB class IV SDN 03 Likmur. Data collection techniques in this study are observations, interviews, tests and documentation. Data analysis in the study is an Interactive Analysis Model by Miles and Huberman with stages of data such as data collection, data reduction, data display, and conclusion drawing/verification. The results of the survey showed that there are kinds of learning difficulties in students in SDN 03 Likes Wealth, among them: 1) Difficulty in understanding concepts, the glory of calculating skills and difficulty in problem solving.